Lithium iron phosphate material and preparation method thereof, positive pole piece and secondary battery
Through step -by -step burning method to control the growth of lithium iron phosphate core, the problem of uneven distribution of lithium iron phosphate materials for traditional iron phosphate material is solved, and the consistency of the material in the discharge process and the high energy effect and excellent circulation performance of the battery.
Patent Information
- Application Number
- CN202411580621.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-01-24
AI Technical Summary
The primary particle size distribution of lithium iron phosphate materials traditionally produced by solid phase method is extremely uneven, resulting in inconsistent during the discharge process, resulting in low battery energy efficiency and poor circulation performance.
Through the step-by-step calcination method, the reaction temperature difference between the first drying material and the second drying material is used to realize the step-by-step nucleation and growth, control the growth rate of the lithium iron phosphate crystal nucleus, and obtain a uniform and concentrated primary particle size distribution. High-strength lithium iron phosphate material.
It achieves the consistency of lithium iron phosphate materials during the discharge process, avoids low energy efficiency caused by large particles and poor cycle performance caused by small particles, ensuring that the battery has both high energy efficiency and excellent cycle performance.
Smart Images

Figure CN119361655A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of battery materials, and in particular to a lithium iron phosphate material and a preparation method thereof, a positive electrode sheet and a secondary battery. Background Art
[0002] Lithium iron phosphate (LFP), with the molecular formula LiFePO4, is a grayish white solid that is insoluble in water and often appears black because it is coated with carbon. Lithium iron phosphate has a wide range of raw materials, is relatively cheap, and is environmentally friendly. It does not contain any heavy metal elements that are harmful to the human body. The oxygen in its olivine structure is difficult to precipitate, and it has good stability. It is a safe positive electrode material for lithium-ion batteries, so it has attracted extensive research and rapid development.
[0003] As the positive electrode material of lithium iron phosphate (such as batteries used in the field of new energy vehicles), the particle size uniformity of lithium iron phosphate materials is very important. However, the primary particle size distribution of lithium iron phosphate materials prepared by traditional solid phase method is extremely uneven, which leads to inconsistency in the discharge process as a positive electrode material, resulting in low battery energy efficiency and poor cycle performance. Summary of the invention
[0004] In view of the technical problems existing in the background technology, the present application provides a lithium iron phosphate material and a preparation method and application thereof, aiming to solve the technical problem of uneven primary particle size distribution of lithium iron phosphate materials prepared by solid phase method in traditional technology.
[0005] In a first aspect, an embodiment of the present application provides a lithium iron phosphate material, wherein the lithium iron phosphate material comprises a core, and the molecular formula of the core is Li a Fe(PO4) b (BO3) c Among them, 1.02≤a≤1.05, 0.98≤b≤1.08, 0.01≤c≤0.02, and the number of particles with a primary particle size of 100nm~600nm accounts for ≥93.5%.
[0006] In the technical solution of the embodiment of the present application, the provided lithium iron phosphate material has a concentrated primary particle size range, and the number of particles with a primary particle size in the range of 100nm~600nm is greater than or equal to 93.5%, so that it has good consistency during the discharge process, avoiding the problems of low energy efficiency caused by large particles and poor cycle performance caused by small particles, thereby ensuring that the battery has the advantages of both high energy efficiency and good cycle performance.
[0007] In some embodiments, the diameter of the primary particles of the lithium iron phosphate material is 0.5-2.5, and the D50 particle size of the primary particle size is 140nm-320nm;
[0008] The compaction density of the lithium iron phosphate material is 2.20 g / mL to 2.60 g / mL, and the BET specific surface area of the lithium iron phosphate material is 8.0 m 2 / g~15.0m 2 / g, and the powder resistivity of the lithium iron phosphate material is 5.00Ω·cm~22.00Ω·cm.
[0009] In this embodiment, the primary particle size of the lithium iron phosphate material is not only evenly distributed but also relatively small, so that the internal arrangement of the lithium iron phosphate material is more uniform, which helps to form a balanced voltage platform and keep the battery stable during operation.
[0010] At the same time, by controlling the compaction density, BET specific surface area and powder resistivity of the lithium iron phosphate material within the above range, it is not only beneficial for the lithium iron phosphate material to have good electronic conductivity and high energy density, but also beneficial for controlling the contact area between the lithium iron phosphate material and the electrolyte, reducing the occurrence of side reactions between the lithium iron phosphate material and the electrolyte, and beneficial for improving the battery's specific capacity, discharge energy efficiency and cycle performance.
[0011] In some embodiments, the lithium iron phosphate material further includes a coating layer, which is coated on the surface of the inner core; wherein the material of the coating layer includes a carbon material, and the mass percentage of the carbon material in the lithium iron phosphate material is 1.10% to 2.00%.
[0012] In this embodiment, the mass fraction of the carbon material in the coating layer to the lithium iron phosphate material is controlled within the above range, which effectively improves the electronic conductivity of the lithium iron phosphate material.
[0013] In a second aspect, an embodiment of the present application provides a method for preparing a lithium iron phosphate material, comprising the following steps:
[0014] Mixing a ferrous source, an oxalate ion source, a borate ion source and a first regulator in a base liquid, and subjecting the mixture to a first reaction treatment;
[0015] The mixture is subjected to a solid-liquid separation process and a first slurry process to obtain a first slurry;
[0016] The first slurry is mixed with a first lithium source, a first phosphorus source and a second regulator, and then subjected to a first grinding treatment and a first drying treatment to obtain a first dried material;
[0017] The trivalent iron source, the second phosphorus source, the second lithium source and the carbon source are mixed, and then subjected to a second slurrying process, a second grinding process and a second drying process to obtain a second dried material;
[0018] The first dried material and the second dried material are mixed and then calcined to obtain the lithium iron phosphate material.
[0019] In the technical scheme of the embodiment of the present application, firstly, raw materials such as ferrous source, oxalate ion source, borate ion source, first lithium source and second phosphorus source are used, and the first dried material with lower reaction temperature required for forming lithium iron phosphate is obtained through stirring reaction, solid-liquid separation, first slurrying, first grinding and first drying. At the same time, raw materials such as trivalent iron source, second phosphorus source, second lithium source and carbon source are used, and the second dried material with higher reaction temperature required for forming lithium iron phosphate is obtained through second slurrying, second grinding and second drying. The first dried material and the second dried material with different reaction temperatures are mixed and calcined, the first dried material first undergoes crystallization reaction to form a crystal nucleus, and the second dried material preferentially nucleates heterogeneously on the crystal nucleus formed by the first dried material and continues to grow, thereby realizing the step-by-step process of nucleation and growth, avoiding the problem of extremely uneven primary particle size distribution caused by disordered growth and instantaneous rapid nucleation of lithium iron phosphate crystal nucleus, and then obtaining a lithium iron phosphate material with uniform primary particle size distribution and high primary particle size concentration.
[0020] In some embodiments, the step of mixing the ferrous source, the oxalate ion source, the borate ion source, and the first regulator in the base solution and obtaining the mixture through a first reaction treatment comprises:
[0021] Mixing the ferrous source, the oxalate ion source, the borate ion source and the first regulator in a base liquid, and subjecting the mixture to a first treatment time at a first temperature to obtain the mixture;
[0022] Wherein, the pH value of the base liquid is 4-5.5, the first temperature is 35° C.-55° C., and the first treatment time is 60 min-120 min.
[0023] In this embodiment, by regulating the pH value, temperature and time in the first reaction treatment process, the generation of ferrous oxalate can be promoted to avoid the reaction to generate trivalent iron products. The decomposition temperature of ferrous oxalate material is low, and its own iron element is divalent iron, and carbon is not required to reduce it under high temperature conditions. Therefore, using ferrous oxalate as a raw material can reduce the temperature of the reaction to generate lithium iron phosphate, thereby forming a crystal nucleus at a lower calcination temperature, which is conducive to the subsequent second drying material to preferentially heterogeneously nucleate on the formed crystal nucleus and continue to grow, thereby realizing the step-by-step nucleation of nucleation and growth, avoiding the disordered growth of lithium iron phosphate crystal nucleus and the problem of extremely uneven primary particle size distribution caused by instantaneous rapid nucleation, and then obtaining a lithium iron phosphate material with uniform primary particle size distribution and high primary particle size concentration.
[0024] In some embodiments, the molar ratio of iron, oxalate and borate in the mixture is 1:(0.8-1):(0.1-0.2);
[0025] The molar ratio of the iron element in the first slurry, the lithium element in the first lithium source, the phosphorus element in the first phosphorus source, and the second regulator is 1:(1.04-1.1):(1.04-1.1):(0.15-0.2);
[0026] The molar ratio of the iron element in the trivalent iron source, the phosphorus element in the second phosphorus source, the lithium element in the second lithium source, and the carbon element in the carbon source is 1:1:(1.02-1.04):(1.2-1.8);
[0027] The molar ratio of the lithium element in the first lithium source to the lithium element in the second lithium source is 1:(8-9).
[0028] In this embodiment, the material amount ratio of the raw materials used in each step is controlled within the above range, which can further improve the uniformity of the primary particle size distribution of the lithium iron phosphate material, greatly reduce the powder resistivity while increasing the compaction density and tap density, thereby showing the advantages of high specific capacity, good rate performance, high discharge energy efficiency and excellent cycle performance.
[0029] In some embodiments, the ferrous source is selected from at least one of ferrous sulfate, ferrous chloride and ferrous acetate, the oxalate ion source includes at least one of oxalic acid, ammonium oxalate and sodium oxalate, the borate ion source includes at least one of boric acid, ammonium borate and sodium borate, and the first regulator includes at least one of ammonium bicarbonate and sodium bicarbonate;
[0030] The first phosphorus source is selected from at least one of phosphoric acid, diammonium hydrogen phosphate and ammonium dihydrogen phosphate, the first lithium source is selected from at least one of lithium oxalate and lithium acetate, and the second regulator includes at least one of polyethylene glycol, polyvinyl alcohol, polyvinyl pyrrolidone and polycarboxylic acid compounds;
[0031] The ferric iron source includes ferric phosphate, the second phosphorus source includes ferric phosphate, the second lithium source includes lithium carbonate, and the carbon source is selected from at least one of glucose, sucrose, starch and cellulose.
[0032] In this embodiment, the selection of a suitable ferrous source, oxalate ion source, borate ion source, first phosphorus source and first lithium source can ensure that the first dried material has a lower reaction temperature, and can dope the lithium iron phosphate material with anions to improve its electrochemical properties. The selection of a suitable trivalent iron source, second phosphorus source, second lithium source and carbon source can ensure that the second dried material has a higher reaction temperature, and can carbon-coat the lithium iron phosphate material to improve its electronic conductivity.
[0033] In some embodiments, the step of mixing the first dried material and the second dried material and then calcining the mixture to obtain the lithium iron phosphate material comprises:
[0034] The first dried material and the second dried material are mixed and crushed to obtain a crushed material, and the crushed material is treated in a first protective atmosphere at a second temperature for a second time, and then at a third temperature for a third time to obtain the lithium iron phosphate material;
[0035] Among them, the D50 particle size of the first dried material is 2μm~5μm, the D50 particle size of the second dried material is 5μm~15μm, the D50 particle size of the crushed material is 0.5μm~1μm, the second temperature is 350℃~450℃, the second processing time is 2h~3h, the third temperature is 600℃~700℃, and the third processing time is 3h~6h.
[0036] In this embodiment, nucleation is induced by a step-by-step calcination method to achieve step-by-step nucleation and growth. Specifically, the reaction temperature required for the first dried material to form lithium iron phosphate is relatively low, and calcination at 350°C to 450°C can fully crystallize and form a crystal nucleus; the reaction temperature required for the second dried material to form lithium iron phosphate is relatively high, and lithium iron phosphate is formed by reacting at 600°C to 700°C, and heterogeneous nucleation and continued growth are preferentially performed on the crystal nucleus formed by the first dried material. At the same time, the particle size of the first dried material, the second dried material and the crushed material is controlled within the above range, and the growth rate of the lithium iron phosphate crystal nucleus can also be regulated to improve the uniformity of the primary particle size of the lithium iron phosphate material. Therefore, the growth of the crystal nucleus can be controlled by the step-by-step calcination method, thereby avoiding the problem of non-concentrated particle distribution caused by instantaneous rapid nucleation, and obtaining a lithium iron phosphate material with a uniform primary particle size distribution and a more concentrated primary particle size.
[0037] In a third aspect, an embodiment of the present application provides a positive electrode plate, including a current collector and a positive electrode material arranged on at least one surface of the current collector along its thickness direction, the positive electrode material including the lithium iron phosphate material as described above or the lithium iron phosphate material prepared by the preparation method as described above.
[0038] In this embodiment, the positive electrode plate and the positive electrode material include the above-mentioned lithium iron phosphate material, and thus have the advantage of improving the battery energy efficiency and cycle performance in the battery.
[0039] In a fourth aspect, an embodiment of the present application provides a secondary battery, comprising a positive electrode sheet, a negative electrode sheet and a separator, wherein the separator is arranged between the positive electrode sheet and the negative electrode sheet, and the positive electrode sheet is the positive electrode sheet mentioned above.
[0040] In this embodiment, the secondary battery includes the above-mentioned positive electrode plate, and thus has the advantages of excellent cycle performance and high energy efficiency.
[0041] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings used in the present application. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0043] Figure 1 A schematic diagram of a process for preparing a lithium iron phosphate material provided in an embodiment of the present application;
[0044] Figure 2 This is a first morphological result diagram of the lithium iron phosphate material obtained in Example 1 of the present application;
[0045] Figure 3 This is a second morphology result diagram of the lithium iron phosphate material obtained in Example 1 of the present application;
[0046] Figure 4 This is a morphology result diagram of the lithium iron phosphate material prepared in Comparative Example 1 of the present application. DETAILED DESCRIPTION
[0047] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0048] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0049] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0050] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0051] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0052] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).
[0053] In the description of the embodiments of the present application, unless otherwise specified, the solvent in the "solution" or "base solution", or "water", is at least one of distilled water, deionized water, pure water, and ultrapure water.
[0054] the term
[0055] Unless otherwise specified or there is a contradiction, the terms and phrases used in this application have the following meanings:
[0056] Particle size: For spherical particles, the particle size refers to the diameter of the spherical particles. For non-spherical particles, the particle size usually refers to the equivalent particle size of the non-spherical particles (generally referred to as the particle size), which can be obtained by using a scanning electron microscope (SEM) or a laser particle size analyzer. Among them, the equivalent particle size means that when a certain physical property of a particle is the same or similar to that of a homogeneous spherical particle, the diameter of the spherical particle is used to represent the diameter of the actual particle. Unless otherwise specified or there is a contradiction, the particle size in this application represents the equivalent particle size.
[0057] Primary particle size: also known as original particle size, refers to the particle size of a single particle, reflecting the intrinsic size of the particles when there is no interaction in the initial stage of formation.
[0058] Secondary particle size: refers to the particle size of aggregates formed by interactions between particles such as agglomeration and coagulation. The secondary particle size is usually larger than the primary particle size and has a wider distribution range.
[0059] Particle size distribution parameters: In the particle size distribution curve of particles, the particle size corresponding to the cumulative particle size distribution percentage reaching N% is called the DN particle size, which means that the particles smaller than this particle size account for N% of all particles, where N=0~100. When N=100, the D100 particle size indicates the particle size corresponding to the cumulative particle size distribution percentage reaching 100%. When N=50, the D50 particle size is the particle size corresponding to the cumulative particle size distribution percentage reaching 50%, indicating the median particle size or median diameter, indicating that particles smaller than and larger than this particle size each account for 50%. For example, D50 particle size = 1mm, which means that particles with a particle size smaller than 1mm and particles with a particle size larger than 1mm each account for 50% of all particles. The DN particle size can be measured by a laser particle size analyzer.
[0060] Span: Also known as span, the calculation formula is: Span = (D90-D10) ÷ D50. The smaller the span, the more concentrated the particle size distribution; the larger the span, the greater the difference in particle size and the more dispersed the distribution.
[0061] In traditional technology, when lithium iron phosphate materials are prepared by the solid phase method, there is a lack of heterogeneous nucleation conditions during the calcination process. All lithium iron phosphates crystallize synchronously, and a large number of lithium iron phosphate nuclei are generated in the same time period. The growth rate of the nuclei is uncontrollable, resulting in extremely uneven distribution of the primary particle size of the lithium iron phosphate material.
[0062] The uneven primary particle size of lithium iron phosphate materials will cause inconsistency in the discharge process. Specifically, large particles discharge slowly, especially large particles with a primary particle size of more than 1μm. The material polarization is large, resulting in a very fast voltage drop during the discharge process, making the energy efficiency low. Small particles discharge quickly, but particles that are too small have a large specific surface area and are more likely to react with trace amounts of decomposed acids or other substances in the electrolyte, causing damage and erosion to the material structure. Therefore, the attenuation in the early stage of the cycle process is very fast, and the cycle performance is significantly deteriorated.
[0063] For energy storage lithium iron phosphate materials, the cycle performance after application in batteries is required to reach 10,000 times or even more than 12,000 times, and the energy efficiency is required to reach 94% or even more than 95% under 0.5P constant power discharge. However, the primary particle size distribution of lithium iron phosphate materials prepared by traditional solid phase synthesis method is extremely uneven, resulting in poor consistency in the discharge process, low battery energy efficiency and deteriorated cycle performance.
[0064] In order to solve the problem of extremely uneven primary particle size distribution of lithium iron phosphate materials prepared by solid phase method in traditional technology, the present application provides a lithium iron phosphate material and its preparation method, positive electrode plate and secondary battery. The primary particle size distribution of the lithium iron phosphate material provided by the present application is uniform and highly concentrated, and has good consistency during the discharge process; the lithium iron phosphate material is prepared by solid phase synthesis method, and through induced nucleation technology, the difference in reaction temperature between the first dried material and the second dried material is used to realize the step-by-step nucleation and growth, effectively controlling the growth rate of the crystal nucleus, so that the primary particle size distribution of the lithium iron phosphate material is more concentrated; the energy efficiency and cycle performance of the positive electrode plate and secondary battery containing the lithium iron phosphate material are also effectively improved.
[0065] In a first aspect, an embodiment of the present application provides a lithium iron phosphate material, wherein the lithium iron phosphate material comprises a core, and the molecular formula of the core is Li a Fe(PO4) b (BO3) c Among them, 1.02≤a≤1.05, 0.98≤b≤1.08, 0.01≤c≤0.02, and the number of particles with a primary particle size of 100nm~600nm accounts for ≥93.5%.
[0066] In the technical solution of the embodiment of the present application, the provided lithium iron phosphate material has a concentrated primary particle size range, and the number of particles with a primary particle size in the range of 100nm~600nm is greater than or equal to 93.5%, so that it has good consistency during the discharge process, avoiding the problems of low energy efficiency caused by large particles and poor cycle performance caused by small particles, thereby ensuring that the battery has the advantages of both high energy efficiency and good cycle performance.
[0067] In this embodiment, in the molecular formula of the kernel, a, b and c all represent stoichiometric ratios. The value of a includes but is not limited to 1.02, 1.025, 1.03, 1.035, 1.04, 1.045, 1.05, etc., the value of b includes but is not limited to 0.98, 0.99, 1.00, 1.01, 1.02, 1.03, 1.04, 1.05, 1.06, 1.07, 1.08, etc., and the value of c includes but is not limited to 0.01, 0.012, 0.014, 0.016, 0.018, 0.02, etc.
[0068] In this embodiment, the number of particles of the lithium iron phosphate material with a primary particle size of 100nm~600nm accounts for ≥93.5%, including but not limited to 93.5%, 94%, 94.5%, 95%, 95.5%, 96%, 96.5%, 97%, 97.5%, 98%, 98.5%, 99%, 99.5%, 100%, etc. Further, the number of particles of the lithium iron phosphate material with a primary particle size of 100nm~600nm accounts for preferably 93.5%~97.3%, and the uniformity of the primary particle size is higher, ensuring that the lithium iron phosphate material has better consistency during the discharge process. Further, the number of particles of the lithium iron phosphate material with a primary particle size of 100nm~600nm accounts for preferably 95.5%~97.3%, and the uniformity of the primary particle size is further improved, and the material has very high consistency during the discharge process.
[0069] In some embodiments, the diameter distance of the primary particles of the lithium iron phosphate material is 0.5-2.5.
[0070] In some embodiments, the D50 particle size of the primary particle size of the lithium iron phosphate material is 140 nm to 320 nm.
[0071] When the lithium iron phosphate material meets the above-mentioned primary particle diameter range, and / or the above-mentioned primary particle D50 particle size range, the primary particle size of the lithium iron phosphate material is not only evenly distributed, but also smaller, so that the internal arrangement of the lithium iron phosphate material is more uniform, which helps to form a balanced voltage platform and keep the battery stable during operation.
[0072] In some embodiments, the diameter distance of the primary particles of the lithium iron phosphate material includes but is not limited to 0.5, 0.6, 0.8, 1.0, 1.2, 1.4, 1.6, 1.8, 2, 2.2, 2.4, 2.5, etc. Further, the diameter distance of the primary particles of the lithium iron phosphate material is preferably 1.2 to 2.5, and the distribution of its primary particle size is more concentrated, so that the consistency of the lithium iron phosphate material during discharge is better, which is beneficial to improving the energy efficiency and cycle performance of the battery. Furthermore, the diameter distance of the primary particles of the lithium iron phosphate material is preferably 1.2 to 1.8, the distribution concentration of the primary particle size is further improved, the discharge consistency is good, and the electrical performance is more excellent.
[0073] In some embodiments, the D50 particle size of the primary particle size of the lithium iron phosphate material includes but is not limited to 140nm, 160nm, 180nm, 200nm, 220nm, 240nm, 260nm, 280nm, 300nm, 320nm, etc. Further, the D50 particle size of the primary particle size of the lithium iron phosphate material is preferably 140nm~305nm, which has a smaller primary particle size, and can achieve close contact and uniform arrangement between lithium iron phosphate material particles, thereby ensuring the stable performance of electrical properties. Further, the D50 particle size of the primary particle size of the lithium iron phosphate material is preferably 160nm~235nm, and the primary particle size is smaller and the distribution is more concentrated, which is conducive to further improving the electrical properties of the material.
[0074] In some embodiments, the compaction density of the lithium iron phosphate material is 2.20 g / mL to 2.60 g / mL.
[0075] In some embodiments, the tap density of the lithium iron phosphate material is 1.00 g / mL to 1.50 g / mL.
[0076] In some embodiments, the BET specific surface area of the lithium iron phosphate material is 8.0 m 2 / g~15.0m 2 / g.
[0077] In some embodiments, the powder resistivity of the lithium iron phosphate material is 5.00 Ω·cm to 22.00 Ω·cm.
[0078] When the lithium iron phosphate material satisfies the above-mentioned compaction density range, and / or the above-mentioned tap density range, and / or the above-mentioned BET specific surface area range, and / or the above-mentioned powder resistivity range, the lithium iron phosphate material not only has good electronic conductivity and good consistency during the discharge process, but also has good compactness between particles of different sizes in the lithium iron phosphate material, thereby improving the electronic conductivity of the lithium iron phosphate material, which is beneficial to improving the specific capacity, discharge energy efficiency and cycle performance of the battery.
[0079] In some embodiments, the compaction density of the lithium iron phosphate material includes but is not limited to 2.20g / mL, 2.25g / mL, 2.30g / mL, 2.35g / mL, 2.40g / mL, 2.45g / mL, 2.50g / mL, 2.55g / mL, 2.60g / mL, etc. Further, the compaction density of the lithium iron phosphate material is preferably 2.25g / mL~2.55g / mL, and the particles of the lithium iron phosphate material are more compact, which can improve the battery's charge and discharge specific capacity, rate performance and energy density, and is conducive to optimizing the battery's cycle life. Furthermore, the compaction density of the lithium iron phosphate material is preferably 2.40g / mL~2.50g / mL, so that the battery's charge and discharge specific capacity, rate performance and cycle performance are more excellent.
[0080] In some embodiments, the tap density of the lithium iron phosphate material is 1.00g / mL~1.50g / mL, including but not limited to 1.00g / mL, 1.05g / mL, 1.10g / mL, 1.15g / mL, 1.20g / mL, 1.25g / mL, 1.30g / mL, 1.35g / mL, 1.40g / mL, 1.45g / mL, 1.50g / mL, etc. Further, the tap density of the lithium iron phosphate material is preferably 1.05g / mL~1.34g / mL, and the particles of the lithium iron phosphate material are in closer contact, which is conducive to increasing energy density, improving rate performance and improving energy efficiency. Furthermore, the tap density of the lithium iron phosphate material is preferably 1.20g / mL~1.32g / mL, so that the battery's charge and discharge specific capacity, rate performance and cycle performance are more excellent.
[0081] In some embodiments, the BET specific surface area of the lithium iron phosphate material is 8.0 m 2 / g~15.0m 2 / g, including but not limited to 8.0m 2 / g, 9m 2 / g, 10m 2 / g, 11m 2 / g, 12m 2 / g, 13m 2 / g, 14m 2 / g, 15.0m 2 / g, etc. Further, the BET specific surface area of the lithium iron phosphate material is preferably 8.01m 2 / g~14.1m 2 / g, the lithium iron phosphate material has a relatively moderate specific surface area. It will not cause too many gaps between particles due to too large specific surface area, thereby hindering the improvement of compaction density, nor will it cause the particle size to be too large due to too small specific surface area, thereby affecting the insertion and extraction of lithium ions. Furthermore, the BET specific surface area of the lithium iron phosphate material is preferably 8.01m 2 / g~11.8m 2 / g, the material has a moderate specific surface area, which further improves the compaction density and promotes the insertion and extraction of lithium ions.
[0082] In some embodiments, the powder resistivity of the lithium iron phosphate material is 5.00Ω·cm~22.00Ω·cm, including but not limited to 5.00Ω·cm, 6Ω·cm, 8Ω·cm, 10Ω·cm, 12Ω·cm, 14Ω·cm, 16Ω·cm, 18Ω·cm, 20Ω·cm, 22.00Ω·cm, etc. Further, the powder resistivity of the lithium iron phosphate material is preferably 6.16Ω·cm~20.40Ω·cm. The lower powder resistivity can speed up the electron transmission speed, improve the charging and discharging efficiency of the battery, meet the needs of fast charging, and at the same time enhance the rate performance, improve the cycle life and improve the safety of the battery. Further, the powder resistivity of the lithium iron phosphate material is preferably 6.16Ω·cm~9.12Ω·cm, and the conductivity of the material is greatly improved, which is conducive to achieving better electrical properties.
[0083] In some embodiments, the lithium iron phosphate material further includes a coating layer, which is coated on the surface of the inner core; wherein the material of the coating layer includes a carbon material, and the mass percentage of the carbon material in the lithium iron phosphate material is 1.10% to 2.00%.
[0084] In this embodiment, the lithium iron phosphate material obtained by carbon coating the inner core can improve the electrical contact between the lithium iron phosphate materials, thereby improving the electronic conductivity of the lithium iron phosphate material.
[0085] In some embodiments, the mass percentage of carbon material in lithium iron phosphate material includes but is not limited to 1.10%, 1.20%, 1.30%, 1.40%, 1.50%, 1.60%, 1.70%, 1.80%, 1.90%, 2.00%, etc. Further, the mass percentage of carbon material in lithium iron phosphate material is preferably 1.45% to 1.98%. An appropriate amount of carbon material can form a complete conductive network on the surface of lithium iron phosphate material, significantly improve the electronic conductivity of the material, and is conducive to adjusting the particle morphology and particle size distribution of the material, thereby improving the charge and discharge specific capacity, rate performance and energy efficiency of the battery.
[0086] See also Figure 1In a second aspect, an embodiment of the present application provides a method for preparing a lithium iron phosphate material, comprising the following steps:
[0087] S1: mixing a ferrous source, an oxalate ion source, a borate ion source and a first regulator in a base liquid, and performing a first reaction treatment to obtain a mixture;
[0088] S2: The mixture is subjected to solid-liquid separation and first slurrying treatment to obtain a first slurry;
[0089] S3: After the first slurry is mixed with the first lithium source, the first phosphorus source and the second regulator, it is subjected to a first grinding treatment and a first drying treatment to obtain a first dried material;
[0090] S4: After the trivalent iron source, the second phosphorus source, the second lithium source and the carbon source are mixed, the mixture is subjected to a second slurrying process, a second grinding process and a second drying process to obtain a second dried material;
[0091] S5: After the first dried material and the second dried material are mixed, they are calcined to obtain lithium iron phosphate material.
[0092] In the technical scheme of the embodiment of the present application, firstly, raw materials such as ferrous source, oxalate ion source, borate ion source, first lithium source and second phosphorus source are used, and the first dried material with lower reaction temperature is obtained through stirring reaction, solid-liquid separation, first slurrying, first grinding and first drying. At the same time, raw materials such as trivalent iron source, second phosphorus source, second lithium source and carbon source are used, and the second dried material with higher reaction temperature is obtained through second slurrying, second grinding and second drying. The first dried material and the second dried material with different reaction temperatures are mixed and calcined, the first dried material first undergoes crystallization reaction to form a crystal nucleus, and the second dried material preferentially nucleates heterogeneously on the crystal nucleus formed by the first dried material and continues to grow, thereby realizing the step-by-step process of nucleation and growth, avoiding the disordered growth of lithium iron phosphate crystal nucleus and instantaneous rapid nucleation, which causes the problem of extremely uneven primary particle size distribution, and then obtaining a lithium iron phosphate material with uniform primary particle size distribution and high concentration.
[0093] The following is a detailed description of the preparation method of lithium iron phosphate material in a step-by-step manner.
[0094] S1: Mixing a ferrous source, an oxalate ion source, a borate ion source and a first regulator in a base liquid, and performing a first reaction treatment to obtain a mixture.
[0095] In some embodiments, the step of mixing a ferrous source, an oxalate ion source, a borate ion source, and a first regulator in a base solution and subjecting the mixture to a first reaction treatment comprises:
[0096] Mixing a ferrous source, an oxalate ion source, a borate ion source and a first conditioning agent in a base liquid, and treating the mixture at a first temperature for a first treatment time to obtain a mixture;
[0097] Among them, the pH value of the base liquid is 4~5.5, the first temperature is 35℃~55℃, and the first processing time is 60min~120min.
[0098] In this embodiment, by regulating the pH value, temperature and time in the first reaction process, the generation of ferrous oxalate material can be promoted to avoid the reaction to generate trivalent iron products. The decomposition temperature of ferrous oxalate material is low, and its own iron element is divalent iron, which does not require high-temperature hot carbon to reduce it. Therefore, using ferrous oxalate as a raw material can reduce the temperature of the reaction to generate lithium iron phosphate, thereby fully crystallizing and forming crystal nuclei at a lower calcination temperature, which is conducive to subsequent induced nucleation.
[0099] It can be understood that the first treatment time includes the first feeding time and the first stirring time. The first feeding time refers to the time for adding the ferrous source, the oxalate ion source, the borate ion source and the first regulator to the base solution, and the first stirring time refers to the time for continuing to stir the reaction after the feeding is completed.
[0100] In some embodiments, the first feeding time and the first stirring time are each independently 30 min to 60 min, including but not limited to 30 min to 60 min, 35 min, 40 min, 45 min, 50 min, 55 min, 60 min, etc.
[0101] In some embodiments, the base liquid is an oxalic acid solution, and the pH value of the base liquid is 4-5.5, including but not limited to 4, 4.2, 4.4, 4.6, 4.8, 5, 5.2, 5.4, 5.5, etc.
[0102] In some embodiments, during the feeding process and during the stirring reaction process, the pH value in the first reaction treatment is maintained at 4~5.5, including but not limited to 4, 4.2, 4.4, 4.6, 4.8, 5, 5.2, 5.4, 5.5, etc.; and the temperature in the first reaction treatment is maintained at 35°C~55°C, including but not limited to 35°C, 37°C, 39°C, 41°C, 43°C, 45°C, 47°C, 49°C, 51°C, 53°C, 55°C, etc.
[0103] In some embodiments, the molar ratio of the iron element in the ferrous source, the oxalate in the oxalate ion source, and the borate in the borate ion source is 1:(0.8-1):(0.1-0.2).
[0104] In this embodiment, the molar ratio of the iron element in the ferrous source to the oxalate in the oxalate ion source is 1:(0.8~1), including but not limited to 1:0.8, 1:0.85, 1:0.9, 1:0.95, 1:1, etc.; the molar ratio of the iron element in the ferrous source to the borate in the borate ion source is 1:(0.1~0.2), including but not limited to 1:0.1, 1:0.12, 1:0.14, 1:0.16, 1:0.18, 1:0.2, etc.; the molar ratio of the oxalate in the oxalate ion source to the borate in the borate ion source is (0.8~1):(0.1~0.2), including but not limited to 0.8:0.1, 0.8:0.2, 0.9:0.1, 0.9:0.2, 1:0.1, 1:0.2, etc.
[0105] In some embodiments, the ferrous source is selected from at least one of ferrous sulfate, ferrous chloride and ferrous acetate, which can be any one of ferrous sulfate, ferrous chloride and ferrous acetate, or a combination of at least two of them, for example: a combination of ferrous sulfate and ferrous chloride, a combination of ferrous sulfate and ferrous acetate, a combination of ferrous chloride and ferrous acetate, or a combination of ferrous sulfate, ferrous chloride and ferrous acetate.
[0106] In some embodiments, the oxalate ion source includes at least one of oxalic acid, ammonium oxalate and sodium oxalate. It can be any one of oxalic acid, ammonium oxalate and sodium oxalate, or a combination of at least two of them, for example: a combination of oxalic acid and ammonium oxalate, a combination of oxalic acid and sodium oxalate, a combination of ammonium oxalate and sodium oxalate, or a combination of oxalic acid, ammonium oxalate and sodium oxalate.
[0107] In some embodiments, the borate ion source includes at least one of boric acid, ammonium borate and sodium borate, which can be any one of boric acid, ammonium borate and sodium borate, or a combination of at least two thereof, for example: a combination of boric acid and ammonium borate, a combination of boric acid and sodium borate, a combination of ammonium borate and sodium borate, or a combination of boric acid, ammonium borate and sodium borate.
[0108] In this embodiment, the borate ion source not only performs anion doping on the lithium iron phosphate to improve the electrochemical properties of the lithium iron phosphate material, but also acts as a flux to further reduce the reaction temperature when the first dried material forms lithium iron phosphate.
[0109] In some embodiments, the first regulator includes at least one of ammonium bicarbonate and sodium bicarbonate. It is understandable that the first regulator is used as an acid-base regulator to adjust the pH value of the reaction system during the feeding process, and it can be ammonium bicarbonate, sodium bicarbonate, or a combination of ammonium bicarbonate and sodium bicarbonate.
[0110] S2: After the mixture is subjected to solid-liquid separation treatment and a first slurry treatment, a first slurry is obtained.
[0111] In some embodiments, the solid-liquid separation treatment in step S2 includes one or more of filtration treatment, suction filtration treatment, filter press treatment and centrifugation treatment, and the present application does not make any special limitation on this.
[0112] In some embodiments, after the solid-liquid separation treatment in step S2, the following step is also included: washing the solid material obtained by the solid-liquid separation treatment until the conductivity of the washing water is ≤200 μS / cm to obtain a washed material.
[0113] In some embodiments, the first slurrying treatment in step S2 includes the following steps: after mixing the washing material and water, pulping treatment is performed to obtain the first slurry.
[0114] In this embodiment, water can be selected from distilled water, reverse osmosis water, deionized water, pure water and ultrapure water, etc., and pure water is more preferred. The solid content of the first slurry is 30% to 40%, including but not limited to 30%, 32%, 34%, 36%, 38%, 40%, etc., and this application does not impose any particular restrictions on this. Among them, the solid content of the first slurry is the mass fraction of the solid in the first slurry.
[0115] S3: After the first slurry is mixed with the first lithium source, the first phosphorus source and the second regulator, it is subjected to a first grinding treatment and a first drying treatment to obtain a first dried material.
[0116] In some embodiments, the ratio of the amount of iron in the first slurry, the lithium in the first lithium source, the phosphorus in the first phosphorus source, and the second regulator is 1:(1.04-1.1):(1.04-1.1):(0.15-0.2);
[0117] In this embodiment, the molar ratio of the iron element in the first slurry to the lithium element in the first lithium source is 1:(1.04~1.1), including but not limited to 1:1.04, 1:1.05, 1:1.06, 1:1.07, 1:1.08, 1:1.09, 1:1.1, etc.; the molar ratio of the iron element in the first slurry to the phosphorus element in the first phosphorus source is 1:(1.04~1.1), including but not limited to 1:1.04, 1:1.05, 1:1.06, 1:1.07, 1:1.08, 1:1.09, 1:1.1, etc.; the molar ratio of the iron element in the first slurry to the second regulator is 1:(0.15~0.2), including but not limited to 1:0.15, 1:0.16, 1:0.17, 1:0.18, 1:0.19, 1:0.2, etc.
[0118] In some embodiments, the first lithium source is selected from at least one of lithium oxalate and lithium acetate, and can be lithium oxalate, lithium acetate, or a combination of lithium oxalate and lithium acetate.
[0119] In this embodiment, the first lithium source is selected from lithium oxalate and lithium acetate with low melting point and low decomposition temperature, which are combined with iron oxalate material with low decomposition temperature and no need for carbon thermal reduction reaction. They can react at a lower reaction temperature to form lithium iron phosphate crystal nuclei, which is beneficial to subsequent induced nucleation.
[0120] In some embodiments, the first phosphorus source is selected from at least one of phosphoric acid, diammonium hydrogen phosphate and ammonium dihydrogen phosphate. It can be selected from any one of phosphoric acid, diammonium hydrogen phosphate and ammonium dihydrogen phosphate, or a combination of at least two of them, for example: a combination of phosphoric acid and diammonium hydrogen phosphate, a combination of phosphoric acid and diammonium dihydrogen phosphate, a combination of diammonium hydrogen phosphate and ammonium dihydrogen phosphate, or a combination of phosphoric acid, diammonium hydrogen phosphate and ammonium dihydrogen phosphate.
[0121] In some embodiments, the second regulator includes at least one of polyethylene glycol, polyvinyl alcohol, polyvinyl pyrrolidone and polycarboxylic acid compounds. The molecular weight of polyethylene glycol can be 200-10000, including but not limited to PEG200, PEG400, PEG600, PEG1000, PEG2000, PEG4000, PEG6000, PEG8000, PEG10000, etc., and PEG6000 is more preferred.
[0122] In this embodiment, the first regulator can be used as a dispersant to improve the dispersion uniformity of the components in the first slurry, thereby allowing the components in the first dry material to be fully mixed, which is beneficial for the full contact and reaction of the components when the first dry material forms lithium iron phosphate under low temperature conditions, thereby improving the product quality of the final lithium iron phosphate material, thereby improving the energy efficiency and cycle performance of batteries using lithium iron phosphate materials.
[0123] In some embodiments, the first grinding process in step S3 includes the following steps: after the first slurry is ground, a first grinding material with a particle size of 0.1 mm to 0.2 mm is obtained.
[0124] In this embodiment, the D50 particle size of the first grinding material is 0.1 mm to 0.2 mm, including but not limited to 0.1 mm, 0.11 mm, 0.12 mm, 0.13 mm, 0.14 mm, 0.15 mm, 0.16 mm, 0.17 mm, 0.18 mm, 0.19 mm, 0.2 mm, etc. The first grinding process can be performed using a ball mill or a sand mill, the inner wall of the grinding equipment is made of ceramic material, and the grinding medium is a ceramic ball of 0.2 mm ± 0.03 mm.
[0125] In some embodiments, the first drying process in step S3 includes the following steps: spray drying the first ground material to obtain a first dried material.
[0126] In some embodiments, the D50 particle size of the first dried material is 2 μm to 5 μm, including but not limited to 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, etc.
[0127] The first dried material obtained by steps S1 to S3 contains raw materials such as lithium oxalate and ferrous oxalate with low melting point and low decomposition temperature, and contains a borate source as a flux to lower the melting point, which is conducive to reacting at a lower reaction temperature to form lithium iron phosphate crystal nuclei and serve as seeds for subsequent heterogeneous nucleation.
[0128] S4: After the trivalent iron source, the second phosphorus source, the second lithium source and the carbon source are mixed, they are subjected to a second slurrying process, a second grinding process and a second drying process to obtain a second dried material.
[0129] In some embodiments, the molar ratio of the iron element in the ferric iron source, the phosphorus element in the second phosphorus source, the lithium element in the second lithium source, and the carbon source is 1:1:(1.02-1.04):(0.2-0.3).
[0130] In this embodiment, the molar ratio of the iron element in the ferric iron source to the phosphorus element in the second phosphorus source is 1:1; the molar ratio of the iron element in the ferric iron source to the lithium element in the second lithium source is 1:(1.02~1.04), including but not limited to 1:1.02, 1:1.025, 1:1.03, 1:1.035, 1.04, etc.; the molar ratio of the iron element in the ferric iron source to the carbon source is 1:(0.2~0.3), including but not limited to 1:0.2, 1:0.21, 1:0.22, 1:0.23, 1:0.24, 1:0.25, 1:0.26, 1:0.27, 1:0.28, 1:0.29, 1:0.3, etc.
[0131] In some embodiments, the first phosphorus source is selected from at least one of phosphoric acid and ammonium dihydrogen phosphate, the first lithium source is selected from at least one of lithium oxalate and lithium acetate, and the second regulator includes polyethylene glycol;
[0132] In some embodiments, the ferric iron source includes ferric phosphate, the second phosphorus source includes ferric phosphate, the second lithium source includes lithium carbonate, and the carbon source is selected from at least one of glucose, sucrose, starch and cellulose. The carbon source can be selected from any one of glucose, sucrose, starch and cellulose, or a combination of at least two thereof, for example: a combination of glucose and sucrose, a combination of glucose and starch, a combination of glucose and cellulose, a combination of sucrose and starch, a combination of sucrose and cellulose, a combination of starch and cellulose, a combination of glucose, sucrose and starch, a combination of glucose, sucrose and starch, and a combination of glucose, sucrose, starch and cellulose.
[0133] In this embodiment, iron phosphate is used as both a trivalent iron source and a phosphorus source, and carbon is required for its reduction reaction under high temperature conditions. At the same time, the lithium source is selected from lithium carbonate with a high melting point and a high decomposition temperature, so that the reaction temperature required for the second dried material to form lithium iron phosphate is relatively high, which is beneficial for the second dried material to preferentially nucleate on the surface of the crystal nucleus obtained from the first dried material through heterogeneous reaction, avoiding disordered growth and instantaneous rapid nucleation, so that the primary particle size distribution of the obtained lithium iron phosphate material is more uniform and concentrated.
[0134] In some embodiments, the molar ratio of the lithium element in the first lithium source to the lithium element in the second lithium source is 1:(8~9), including but not limited to 1:8, 1:8.1, 1:8.2, 1:8.3, 1:8.4, 1:8.5, 1:8.6, 1:8.7, 1:8.8, 1:8.9 or 1:9.
[0135] In this embodiment, by regulating the ratio of the amount of substance of the two lithium sources, the mass ratio of the first dry material and the second dry material can be regulated, and then the mass ratio of the lithium iron phosphate generated at different reaction temperatures can be accurately regulated, which is conducive to obtaining a lithium iron phosphate material with a more concentrated primary particle size distribution. Specifically, if the ratio of the amount of substance of the lithium element in the first lithium source and the lithium element in the second lithium source is less than 1:9, the amount of the first lithium source is less, the mass of the first dry material obtained by the reaction is less, and the number of crystal nuclei formed by crystallization in advance during the calcination process is less, and it is impossible to provide sufficient phase interface for subsequent heterogeneous nucleation, and there are phenomena such as disordered growth of crystal nuclei and instantaneous rapid nucleation, which ultimately leads to uneven primary particle size distribution. If the ratio of the amount of substance of the lithium element in the first lithium source and the lithium element in the second lithium source is higher than 1:8, the amount of the first lithium source is more, and the number of crystal nuclei formed by crystallization in advance is too large, so that some crystal nuclei do not participate in subsequent heterogeneous nucleation, which will eventually cause uneven primary particle size distribution of lithium iron phosphate material.
[0136] In some embodiments, the second slurrying treatment in step S4 includes the following steps: after the trivalent iron source, the second phosphorus source, the second lithium source and the carbon source are mixed, water is added for slurrying to obtain a second slurry.
[0137] In this embodiment, water can be selected from distilled water, reverse osmosis water, deionized water, pure water and ultrapure water, etc., and pure water is more preferred. The solid content of the second slurry is 30% to 40%, including but not limited to 30%, 32%, 34%, 36%, 38%, 40%, etc., and this application does not make any special restrictions on this. Among them, the solid content of the second slurry is the mass fraction of the solid in the first slurry.
[0138] In some embodiments, the second grinding process in step S4 includes the following steps: after the second slurry is ground, a second grinding material with a particle size of 0.2 μm to 0.5 μm is obtained.
[0139] In this embodiment, the D50 particle size of the second abrasive is 0.2 μm to 0.5 μm, including but not limited to 0.2 μm, 0.25 μm, 0.3 μm, 0.35 μm, 0.4 μm, 0.45 μm, 0.5 μm, etc. The second grinding process can be performed using a ball mill or a sand mill, the inner wall of the grinding equipment is made of ceramic material, and the grinding medium is a ceramic ball of 0.3 mm ± 0.03 mm.
[0140] In some embodiments, the second drying process in step S4 includes the following steps: spray drying the second ground material to obtain a second dried material.
[0141] In some embodiments, the D50 particle size of the second dried material is 5 μm to 15 μm, including but not limited to 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, etc.
[0142] S5: After the first dried material and the second dried material are mixed, they are calcined to obtain lithium iron phosphate material.
[0143] In some embodiments, the step of mixing the first dried material and the second dried material and then calcining the mixture to obtain the lithium iron phosphate material comprises:
[0144] The first dried material and the second dried material are mixed and crushed to obtain a crushed material;
[0145] The crushed material is treated in a first protective atmosphere at a second temperature for a second treatment time, and then at a third temperature for a third treatment time to obtain a lithium iron phosphate material;
[0146] Among them, the D50 particle size of the crushed material is 0.5μm~1μm, the second temperature is 350℃~450℃, the second processing time is 2h~3h, the third temperature is 600℃~700℃, and the third processing time is 3h~6h.
[0147] In this embodiment, nucleation is induced by a step-by-step calcination method to achieve step-by-step nucleation and growth. Specifically, the chemical reaction temperature of the first dried material is relatively low, and calcination at 350°C to 450°C can fully crystallize it and form a crystal nucleus; the reaction temperature of the second dried material is relatively high, and it will react at 600°C to 700°C to form lithium iron phosphate, and preferentially perform heterogeneous nucleation and continue to grow on the crystal nucleus formed by the first dried material. Therefore, the growth rate of the crystal nucleus can be controlled by the step-by-step calcination method, thereby avoiding the problem of non-concentrated particle distribution caused by instantaneous rapid nucleation, and obtaining a lithium iron phosphate material with a more concentrated primary particle size distribution.
[0148] In this embodiment, the D50 particle size of the pulverized material is 0.5 μm to 1 μm, including but not limited to 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, etc. The pulverization of the mixed first dried material and the second dried material can be performed by a mechanical pulverizer or a jet pulverizer.
[0149] In this embodiment, the second temperature is 350℃~450℃, including but not limited to 350℃, 360℃, 370℃, 380℃, 390℃, 400℃, 410℃, 420℃, 430℃, 440℃, 450℃, etc.; the second treatment time is 2h~3h, including but not limited to 2h, 2.1h, 2.2h, 2.3h, 2.4h, 2.5h, 2.6h, 2.7h, 2.8h, 2.9h, 3h, etc.; the third temperature is 600℃~700℃, including but not limited to 600℃, 610℃, 620℃, 630℃, 640℃, 650℃, 660℃, 670℃, 680℃, 690℃, 700℃, etc.; the third treatment time is 3h~6h, including but not limited to 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h.
[0150] In some embodiments, the rate of heating from room temperature to the second temperature is 100°C / h~150°C / h, including but not limited to 100°C / h, 110°C / h, 120°C / h, 130°C / h, 140°C / h, 150°C / h, etc.; the rate of heating from the second temperature to the third temperature is 30°C / h~50°C / h, including but not limited to 30°C / h, 35°C / h, 40°C / h, 45°C / h, 50°C / h, etc.
[0151] In some embodiments, the first protective atmosphere satisfies: oxygen content is less than 1 ppm, and humidity is less than 1%. The oxygen content is less than 1 ppm by introducing a protective gas, and the protective gas includes but is not limited to nitrogen, helium, neon, argon, xenon, etc., and nitrogen is more preferably used. During the calcination process, the induced draft fan is turned on in the temperature rising section to ensure that the humidity in the heat preservation section is less than 1%.
[0152] In some embodiments, after the calcination treatment, the following steps are further included: obtaining lithium iron phosphate material through the steps of crushing, screening, iron removal and packaging.
[0153] In some embodiments, the pulverization process after calcination is carried out using a fluidized bed airflow mill under a protective atmosphere. Specifically, a Laval nozzle is used in the pulverization chamber of the fluidized bed airflow mill to make the airflow velocity reach Mach 2 to Mach 3, thereby disturbing the collision of the material for pulverization. The protective atmosphere includes but is not limited to nitrogen, helium, neon, argon, xenon, etc., and nitrogen is further preferred; the pressure of the protective atmosphere is 0.4MPa~0.8MPa, including but not limited to 0.4MPa, 0.5MPa, 0.6MPa, 0.7MPa, 0.8MPa, etc.; the temperature of the protective atmosphere is 100℃~150℃, including but not limited to 100℃, 110℃, 120℃, 130℃, 140℃, 150℃, etc.
[0154] In some embodiments, the crushed material is classified in a classification chamber using a classification wheel, and the classified material is sieved using an ultrasonic vibration screen. The sieving, iron removal and packaging are all carried out in a constant temperature and humidity room.
[0155] In a third aspect, an embodiment of the present application provides a positive electrode plate, including a current collector and a positive electrode material arranged on at least one surface of the current collector along its thickness direction, the positive electrode material including the lithium iron phosphate material as described above or the lithium iron phosphate material prepared by the preparation method as described above.
[0156] In this embodiment, the positive electrode plate and the positive electrode material include the above-mentioned lithium iron phosphate material, and thus have the advantage of good discharge performance.
[0157] In a fourth aspect, an embodiment of the present application provides a secondary battery, comprising a positive electrode sheet, a negative electrode sheet and a separator, wherein the separator is arranged between the positive electrode sheet and the negative electrode sheet, and the positive electrode sheet is the above-mentioned positive electrode sheet.
[0158] In this embodiment, the secondary battery includes the above-mentioned positive electrode plate, and thus has the advantages of excellent cycle performance and high energy efficiency.
[0159] Some specific embodiments are listed below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be obtained commercially.
[0160] 1. Preparation method
[0161] Example 1
[0162] The preparation method of the lithium iron phosphate material provided in this embodiment comprises the following steps:
[0163] (1) Add a ferrous source, an oxalate ion source, a borate ion source and a first regulator into the base liquid. During the feeding process, the pH value is maintained at 4.5 and the temperature is maintained at 45° C. The feeding time is 50 min, and then the stirring reaction is continued for 40 min to obtain a mixture.
[0164] Among them, the ferrous source is ferrous sulfate solution, the oxalate ion source is oxalic acid solution, the borate ion source is boric acid solution, the first regulator is ammonium bicarbonate, and the base liquid is oxalic acid base liquid with a pH value of 4.5; the molar ratio of iron element, oxalate and borate in the mixture is 1:0.9:0.1.
[0165] (2) filtering the mixture to obtain a solid material; washing the solid material with pure water until the conductivity of the washing water is ≤200 μS / cm to obtain a washed material; adding pure water to the washed material for a first slurry treatment to obtain a first slurry with a solid content of 35 wt %.
[0166] (3) Adding a first lithium source, a first phosphorus source and a second regulator to the first slurry, stirring and dissolving them, and then performing a first grinding treatment in a ball mill, wherein the inner wall of the ball mill is made of ceramic material and the grinding medium is a ceramic ball of 0.2 mm ± 0.03 mm, to obtain a first grinding material with a particle size of 0.15 mm; spray drying the first grinding material to obtain a first dried material with a particle size of 3.5 μm.
[0167] Among them, the first lithium source is lithium oxalate; the first phosphorus source is a mixed solution containing phosphoric acid and diammonium phosphate, and the pH value of the mixed solution is 2.9; the second regulator is PEG6000; the molar ratio of the iron element in the first slurry, the lithium element in the first lithium source, the phosphorus element in the first phosphorus source and the second regulator is 1:1.06:1.08:0.18.
[0168] (4) After mixing the trivalent iron source, the second phosphorus source, the second lithium source and the carbon source, water is added to perform a second slurry treatment to obtain a second slurry with a solid content of 35%; the second slurry is subjected to a second grinding treatment using a ball mill, wherein the inner wall of the ball mill is made of ceramic material and the grinding medium is a ceramic ball of 0.3 mm ± 0.03 mm, to obtain a second abrasive with a particle size of 0.34 μm; the second abrasive is spray dried to obtain a second dried material with a particle size of 12 μm.
[0169] Among them, the trivalent iron source and the second phosphorus source are both iron phosphate, the second lithium source is lithium carbonate, and the carbon source is glucose; the molar ratio of the iron element or phosphorus element in the iron phosphate, the lithium element in the lithium carbonate and the glucose is 1:1.03:0.25; the molar ratio of the lithium element in the first lithium source and the lithium element in the second lithium source is 1:8.5.
[0170] (5) After mixing the first dried material and the second dried material, the materials were crushed to a particle size of 0.8 μm using a jet mill to obtain a crushed material; the crushed material was calcined in a roller furnace, and nitrogen was introduced to maintain the oxygen content in the roller furnace below 1 ppm. At the same time, the induced draft fan was turned on in the heating section to make the humidity in the insulation section below 1%. The materials were first heated to 400°C at a heating rate of 120°C / h and kept at this temperature for 2.5 hours, then heated to 600°C at a heating rate of 40°C / h and kept at this temperature for 5 hours, and then cooled to a temperature of ≤100°C before being taken out of the furnace.
[0171] (6) After the calcined material is taken out of the furnace, it is crushed by a fluidized bed airflow mill. The crushing process is carried out in a nitrogen atmosphere with a pressure of 0.6 MPa and a temperature of 135°C. A Laval nozzle is used in the crushing chamber to make the air flow velocity reach 2.5 Mach, disturbing the collision of the material for crushing; the crushed material is classified in the classification chamber by a classifying wheel, and the classified material is screened by an ultrasonic vibrating screen. The screening, iron removal and packaging are all carried out in a constant temperature and humidity room, thereby obtaining lithium iron phosphate material.
[0172] Example 2
[0173] The preparation method of the lithium iron phosphate material provided in this embodiment comprises the following steps:
[0174] (1) Add a ferrous source, an oxalate ion source, a borate ion source and a first regulator into the base liquid. During the feeding process, the pH value is maintained at 4 and the temperature is maintained at 35° C. The feeding time is 30 min, and then the stirring reaction is continued for 30 min to obtain a mixture.
[0175] Among them, the ferrous source is ferrous acetate, the oxalate ion source is oxalic acid, the borate ion source is boric acid, the first regulator is sodium bicarbonate, and the base liquid is an oxalic acid base liquid with a pH value of 4; the molar ratio of iron element, oxalate and borate in the mixture is 1:0.8:0.1.
[0176] (2) filtering the mixture to obtain a solid material; washing the solid material with pure water until the conductivity of the washing water is ≤200 μS / cm to obtain a washed material; adding pure water to the washed material for a first slurry treatment to obtain a first slurry with a solid content of 35%.
[0177] (3) Adding a first lithium source, a first phosphorus source and a second regulator to the first slurry, stirring and dissolving, and then performing a first grinding treatment using a sand mill, wherein the inner wall of the sand mill is made of ceramic material and the grinding medium is a ceramic ball of 0.2 mm ± 0.03 mm, to obtain a first abrasive with a particle size of 0.1 mm; spray drying the first abrasive to obtain a first dried material with a particle size of 2 μm.
[0178] Among them, the first lithium source is lithium oxalate; the first phosphorus source is a mixed solution containing phosphoric acid and diammonium phosphate, with a pH value of 2.5; the second regulator is PEG6000; the molar ratio of the iron element in the first slurry, the lithium element in the first lithium source, the phosphorus element in the first phosphorus source and the second regulator is 1:1.04:1.04:0.15.
[0179] (4) After mixing the trivalent iron source, the second phosphorus source, the second lithium source and the carbon source, water is added to perform a second slurry treatment to obtain a second slurry with a solid content of 35%; the second slurry is subjected to a second grinding treatment using a sand mill, wherein the inner wall of the sand mill is made of ceramic material and the grinding medium is a ceramic ball of 0.3 mm ± 0.03 mm, to obtain a second abrasive with a particle size of 0.2 μm; the second abrasive is spray dried to obtain a second dried material with a particle size of 5 μm.
[0180] Among them, the trivalent iron source and the second phosphorus source are both iron phosphate, the second lithium source is lithium carbonate, and the carbon source is glucose; the molar ratio of the iron element or phosphorus element in the iron phosphate, the lithium element in the lithium carbonate and the glucose is 1:1.02:0.2; the molar ratio of the lithium element in the first lithium source and the lithium element in the second lithium source is 1:8.
[0181] (5) After mixing the first dried material and the second dried material, the materials were crushed to a particle size of 0.5 μm using a jet mill to obtain a crushed material; the crushed material was calcined in a roller furnace, and nitrogen was introduced to maintain the oxygen content in the roller furnace below 1 ppm. At the same time, the induced draft fan was turned on in the heating section to make the humidity in the insulation section below 1%. The materials were first heated to 350°C at a heating rate of 100°C / h and kept at this temperature for 2 h, then heated to 600°C at a heating rate of 30°C / h and kept at this temperature for 3 h, and then cooled to a temperature of ≤100°C before being taken out of the furnace.
[0182] (6) After the calcined material is taken out of the furnace, it is crushed by a fluidized bed airflow mill. The crushing process is carried out in a nitrogen atmosphere with a pressure of 0.4 MPa and a temperature of 100°C. A Laval nozzle is used in the crushing chamber to make the air flow velocity reach 2 Mach, disturbing the collision of the material for crushing; the crushed material is classified in the classification chamber by a classifying wheel, and the classified material is screened by an ultrasonic vibrating screen. The screening, iron removal and packaging are all carried out in a constant temperature and humidity room, thereby obtaining lithium iron phosphate material.
[0183] Example 3
[0184] The preparation method of the lithium iron phosphate material provided in this embodiment comprises the following steps:
[0185] (1) A ferrous source, an oxalate ion source, a borate ion source and a first regulator are added to the base liquid. During the feeding process, the pH value is maintained at 5.5 and the temperature is maintained at 55° C. The feeding time is 60 min, and then the stirring reaction is continued for 60 min to obtain a mixture.
[0186] Among them, the ferrous source is ferrous sulfate solution, the oxalate ion source is oxalic acid solution, the borate ion source is boric acid solution, the first regulator is ammonium bicarbonate, and the base liquid is oxalic acid base liquid with a pH value of 5.5; the molar ratio of iron element, oxalate and borate in the mixture is 1:1:0.2.
[0187] (2) filtering the mixture to obtain a solid material; washing the solid material with pure water until the conductivity of the washing water is ≤200 μS / cm to obtain a washed material; adding pure water to the washed material for a first slurry treatment to obtain a first slurry with a solid content of 40%.
[0188] (3) Adding a first lithium source, a first phosphorus source and a second regulator to the first slurry, stirring and dissolving them, and then performing a first grinding treatment in a ball mill, wherein the inner wall of the ball mill is made of ceramic material and the grinding medium is a ceramic ball of 0.2 mm ± 0.03 mm, to obtain a first grinding material with a particle size of 0.2 mm; spray drying the first grinding material to obtain a first dried material with a particle size of 5 μm.
[0189] Among them, the first lithium source is lithium oxalate; the first phosphorus source is a mixed solution containing phosphoric acid and diammonium phosphate, with a pH value of 2.9; the second regulator is PEG6000; the molar ratio of the iron element in the first slurry, the lithium element in the first lithium source, the phosphorus element in the first phosphorus source and the second regulator is 1:1.1:1.1:0.2.
[0190] (4) After mixing the trivalent iron source, the second phosphorus source, the second lithium source and the carbon source, water is added for a second slurry treatment to obtain a second slurry with a solid content of 40 wt%; the second slurry is subjected to a second grinding treatment using a ball mill, wherein the inner wall of the ball mill is made of ceramic material and the grinding medium is a ceramic ball of 0.3 mm ± 0.03 mm, to obtain a second abrasive with a particle size of 0.5 μm; the second abrasive is spray dried to obtain a second dried material with a particle size of 15 μm.
[0191] Among them, the trivalent iron source and the second phosphorus source are both iron phosphate, the second lithium source is lithium carbonate, and the carbon source is glucose; the molar ratio of the iron element or phosphorus element in the iron phosphate, the lithium element in the lithium carbonate and the glucose is 1:1.03:0.25; the molar ratio of the lithium element in the first lithium source and the lithium element in the second lithium source is 1:9.
[0192] (5) After mixing the first dried material and the second dried material, the materials were crushed to a particle size of 1 μm using a jet mill to obtain a crushed material; the crushed material was calcined in a roller furnace, and nitrogen was introduced to maintain the oxygen content in the roller furnace below 1 ppm. At the same time, the induced draft fan was turned on in the heating section to make the humidity in the insulation section below 1%. The temperature was first increased to 450°C at a heating rate of 150°C / h and kept at this temperature for 3 hours, and then increased to 700°C at a heating rate of 50°C / h and kept at this temperature for 6 hours. The sintered material was cooled to a temperature ≤100°C before being taken out of the furnace.
[0193] (6) After the calcined material is taken out of the furnace, it is crushed by a fluidized bed air flow mill. The crushing process is carried out in a nitrogen atmosphere with a pressure of 0.8 MPa and a temperature of 150°C. A Laval nozzle is used in the crushing chamber to make the air flow velocity reach 3 Mach, disturbing the collision of the material for crushing; the crushed material is classified in the classification chamber by a classifying wheel, and the classified material is screened by an ultrasonic vibrating screen. The screening, iron removal and packaging are all carried out in a constant temperature and humidity room, thereby obtaining lithium iron phosphate material.
[0194] Example 4
[0195] The preparation method of the lithium iron phosphate material provided in this embodiment is the same or similar to that in Embodiment 1, except that:
[0196] In step (4), the molar ratio of the iron element or phosphorus element in the ferric phosphate, the lithium element in the lithium carbonate and the glucose is 1:1.04:0.3.
[0197] Example 5
[0198] The preparation method of the lithium iron phosphate material provided in this embodiment is the same or similar to that in Embodiment 1, except that:
[0199] In step (1), the ferrous source is replaced by a ferrous chloride solution, the oxalate ion source is an ammonium oxalate solution, and the borate ion source is an ammonium borate solution.
[0200] Example 6
[0201] The preparation method of the lithium iron phosphate material provided in this embodiment is the same or similar to that in Embodiment 1, except that:
[0202] In step (1), the ferrous source is replaced by an equimolar amount of ferrous acetate solution, the oxalate ion source is a sodium oxalate solution, and the borate ion source is a sodium borate solution;
[0203] In step (3), the first lithium source is lithium acetate.
[0204] Example 7
[0205] The preparation method of the lithium iron phosphate material provided in this embodiment is the same or similar to that in Embodiment 1, except that:
[0206] In step (1), the molar ratio of iron, oxalate and borate in the mixture is 1:0.6:0.05;
[0207] In step (3), the molar ratio of the iron element in the first slurry, the lithium element in the first lithium source, the phosphorus element in the first phosphorus source, and the second regulator is 1:1:1.02:0.12.
[0208] Example 8
[0209] The preparation method of the lithium iron phosphate material provided in this embodiment is the same or similar to that in Embodiment 1, except that:
[0210] In step (1), the molar ratio of iron, oxalate and borate in the mixture is 1:1.2:0.3;
[0211] In step (3), the molar ratio of the iron element in the first slurry, the lithium element in the first lithium source, the phosphorus element in the first phosphorus source, and the second regulator is 1:1.2:1.2:0.3.
[0212] Example 9
[0213] The preparation method of the lithium iron phosphate material provided in this embodiment is the same or similar to that in Embodiment 1, except that:
[0214] In step (4), the molar ratio of the iron element or phosphorus element in the iron phosphate, the lithium element in the lithium carbonate and the glucose is 1:0.96:0.18.
[0215] Example 10
[0216] The preparation method of the lithium iron phosphate material provided in this embodiment is the same or similar to that in Embodiment 1, except that:
[0217] In step (4), the molar ratio of the iron element or phosphorus element in the iron phosphate, the lithium element in the lithium carbonate and the glucose is 1:1.10:0.35.
[0218] Embodiment 11
[0219] The preparation method of the lithium iron phosphate material provided in this embodiment is the same or similar to that in Embodiment 1, except that:
[0220] In step (4), the molar ratio of the lithium element in the first lithium source to the lithium element in the second lithium source is 1:7.
[0221] Example 12
[0222] The preparation method of the lithium iron phosphate material provided in this embodiment is the same or similar to that in Embodiment 1, except that:
[0223] In step (4), the molar ratio of the lithium element in the first lithium source to the lithium element in the second lithium source is 1:10.
[0224] Comparative Example 1
[0225] Compared with Example 1, the process of preparing the first dried material is omitted, and the second dried material obtained in step (4) is directly calcined according to step (5), and crushed, screened, iron-removed and packaged according to step (6) to obtain lithium iron phosphate material.
[0226] Comparative Example 2
[0227] Compared with Example 1, there is no process for preparing the second dried material. After the first dried material is prepared according to steps (1) to (3), the first dried material is calcined according to step (5), and crushed, screened, iron-removed and packaged according to step (6) to obtain lithium iron phosphate material.
[0228] 2. Test Method
[0229] 1. Properties of positive electrode materials
[0230] 1. SEM test: The morphology of lithium iron phosphate material was characterized by using MERLIN Compact and Quanta 200FEG field emission scanning electron microscope (SEM) produced by Zeiss. The results are shown in Figure 2~Figure 3 .in, Figure 2 This is a first morphological result diagram of the lithium iron phosphate material obtained in Example 1 of the present application. Figure 3 This is a second morphology result diagram of the lithium iron phosphate material obtained in Example 1 of the present application. Figure 4 This is a morphology result diagram of the lithium iron phosphate material prepared in Comparative Example 1 of the present application.
[0231] 2. Element content: Use Inductively Coupled PlasmaOptical Emission Spectrometer (ICP-OES) to test the content of each element in the lithium iron phosphate material.
[0232] 3. BET specific surface area: measured by gas adsorption BET method.
[0233] 4. Powder resistivity: tested by four-probe method, the test pressure is 10MPa.
[0234] 5. Compaction density: Tested by compaction density meter, the test pressure is 3T, and the pressing time is 30S.
[0235] 6. Tap density: tested with a tap density meter with 5000 vibrations.
[0236] 7. pH value: refer to GB / T 9724-2007 General Rules for Determination of pH Value of Chemical Reagents.
[0237] 8. Diameter distance of primary particles: The D10, D50 and D90 diameters of primary particles are measured by a laser particle size analyzer, and the diameter distance of primary particles is calculated according to (D90-D10)÷D50.
[0238] 9. D50 particle size of primary particles: observed using SEM.
[0239] 10. Free Li: measured by automatic potentiometric titration.
[0240] 11. Iron dissolution: Add 10 g of the sample to be tested into 100 mL of 0.1 mol / L hydrogen fluoride-ethanol solution, stir and dissolve at 45°C for 30 min, then filter. Use ICP-OES to measure the iron content in the filtrate, which is the iron dissolution amount.
[0241] (II) Property test of secondary batteries
[0242] The lithium iron phosphate materials prepared in each embodiment and comparative example were mixed with superfine carbon powder (Super P, SP) and polyvinylidene fluoride PVDF in a mass ratio of 92:4:4, and then N-methylpyrrolidone (NMP) was added for slurrying, and then coated on aluminum foil, and then dried and pressed into sheets. Then, a lithium sheet was used as a negative electrode, lithium hexafluorophosphate (LiPF6) was used as a lithium salt, and ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) with a volume ratio of 1:1:1 were used as organic solvents. The lithium salt was dissolved in the organic solvent to prepare an electrolyte with a concentration of 1M to prepare a button battery. Then, its charge specific capacity and discharge specific capacity were measured at 0.1C and 1C rates, and its discharge energy efficiency was tested at a discharge rate of 0.5P. The test temperature was 25°C and the voltage range was 2.0-3.75V.
[0243] III. Analysis of test results of various embodiments and comparative examples
[0244] The results obtained according to the above test method are shown in Tables 1 to 3 respectively.
[0245] Table 1
[0246]
[0247] Table 2
[0248]
[0249] Table 3
[0250]
[0251] As shown in Table 1, the mass fractions of the elements in the lithium iron phosphate materials obtained in Examples 1 to 12 are as follows: 4.76% to 5.98% for Li, 24.15% to 35.78% for Fe, 18.05% to 20.89% for P, 367ppm to 1258ppm for B, and 1.45% to 1.98% for C. It can be inferred that the lithium iron phosphate material includes a core and a coating layer coated on the surface of the core, wherein the molecular formula of the core is Li a Fe(PO4) b (BO3) c , 1.02≤a≤1.05, 0.98≤b≤1.08, 0.01≤c≤0.02, the coating layer includes a carbon material, and the mass percentage of the carbon material in the lithium iron phosphate material is 1.45%~1.98%.
[0252] Combined with Table 1 and Figure 2~Figure 4It can be seen that the D50 particle size of the primary particles of the lithium iron phosphate material prepared by the traditional solid phase method in Comparative Example 1 is 325nm, the diameter distance of the primary particles is 4.8, and the number of particles with a primary particle size of 100nm~600nm accounts for only 91.5%, indicating that the distribution of its primary particle size is uneven. Comparative Example 2 uses the first dried material with a lower reaction temperature for calcination, crushing, screening and other treatments. The D50 particle size of the primary particles of the lithium iron phosphate material obtained is very small, but the diameter distance of the primary particles reaches 6.1, and the number of particles with a primary particle size of 100nm~600nm accounts for only 92.1%, indicating that the distribution of its primary particle size is also uneven. The lithium iron phosphate material obtained in Examples 1 to 12 has a primary particle D50 particle size of 142nm to 305nm, a primary particle diameter of 1.2 to 2.5, and a primary particle diameter of 100nm to 600nm, accounting for 93.5% to 97.3%. Compared with the lithium iron phosphate material obtained in Comparative Examples 1 to 2, the primary particle size distribution is more uniform and the primary particle D50 particle size is smaller, indicating that Examples 1 to 12 effectively adjust the growth rate of the lithium iron phosphate nucleus through the coordinated cooperation of the first drying material and the second drying material with different reaction temperatures, and realize the step-by-step nucleation and growth, thereby obtaining a lithium iron phosphate material with a uniform primary particle size distribution and a smaller primary particle size. At the same time, the lithium iron phosphate material obtained in Examples 1 to 6 has a smaller diameter, and the number of particles with a primary particle size of 100nm to 600nm accounts for a higher proportion, indicating that the precise control of the amount ratio of each raw material can improve the uniformity of the primary particle size distribution.
[0253] As shown in Table 2, the compacted density of the lithium iron phosphate materials prepared in Examples 1 to 12 is 2.25 g / mL to 2.55 g / mL, the tapped density is 1.05 g / mL to 1.34 g / mL, and the BET specific surface area is 8.1 m 2 / g~14.1m 2 / g, the powder resistivity is 6.16Ω·cm~20.4Ω·cm, the free Li content is 213ppm~986ppm, the iron dissolution amount is 14.7ppm~125.8ppm, and the pH value is 8.38~10.89. At the same time, the compacted density of the lithium iron phosphate material of Examples 1 to 6 is above 2.41g / mL, the tapped density is above 1.21g / mL, and the BET specific surface area is above 11.8m 2 / g or less, powder resistivity or less than 9.12Ω·cm, free Li content or less than 548ppm, iron dissolution amount or less than 17.5ppm, and pH value or less than 8.57-9.13, indicating that controlling the molar ratio of each raw material within a suitable range is conducive to obtaining higher compacted density and tapped density, more suitable BET specific surface area, lower powder resistivity, lower free Li content, lower iron dissolution content and suitable pH value.
[0254] Compared with Example 1, the molar ratio of the lithium element in the first lithium source to the lithium element in the second lithium source in Examples 11-12 is not controlled within the range of 1: (8-9), which results in a significant decrease in the compacted density and tap density of the lithium iron phosphate material obtained in Example 11, a high BET specific surface area, and a significant increase in the powder resistivity. Although the lithium iron phosphate material obtained in Example 12 has a higher compacted density and tap density, its powder resistivity is more than twice that of the powder resistivity of Example 1, which means that the conductivity of the lithium iron phosphate material obtained in Example 12 is significantly deteriorated, thereby affecting the charge and discharge specific capacity, rate performance, energy efficiency and cycle performance. This shows that controlling the feed ratio of the first lithium source and the second lithium source is beneficial to significantly reduce the powder resistivity of the lithium iron phosphate material while improving the compacted density and tap density, so that its conductivity is greatly improved, which is conducive to achieving better electrical properties.
[0255] Compared with Comparative Examples 1 and 2, the powder resistivity of the lithium iron phosphate material obtained in Example 1 is greatly reduced, which proves that the uniformity of the primary particle size distribution can significantly reduce the powder resistivity of the lithium iron phosphate material, improve its conductivity, and make it have good consistency during the discharge process. At the same time, compared with Comparative Example 1, the specific surface area of the lithium iron phosphate material obtained in Example 1 is significantly increased, which means that the contact area between the lithium iron phosphate material and the electrolyte is larger, and the channels for ion transmission and electron conduction are increased, which is conducive to reducing internal resistance, increasing specific capacity, and improving rate performance; Compared with Comparative Example 2, the compacted density and tap density of the lithium iron phosphate material obtained in Example 1 are higher, the BET specific surface area is more moderate, and the free Li content, iron dissolution amount and pH value are reduced, which proves that the coordinated cooperation of the first dried material and the second dried material can ensure the uniformity of the primary particle size distribution while obtaining a more suitable specific surface area of the lithium iron phosphate material, and improve the compacted density, tap density and other properties of the lithium iron phosphate material.
[0256] As shown in Table 3, the 0.1C first charge specific capacity of the lithium iron phosphate material prepared in Examples 1 to 12 is 160.5mAh / g to 163.5mAh / g, the 0.1C first discharge specific capacity is 157.6mAh / g to 159.9mAh / g, the 1C first charge specific capacity is 143.7mAh / g to 148.9mAh / g, the 1C first discharge specific capacity is 144.8mAh / g to 147.9mAh / g, and the 0.5P discharge energy efficiency is 94.6 0%~95.50%, and the room temperature cycle capacity retention rate after 1000 cycles at 1C rate is 97.6%~98.5%. Its specific capacity, rate performance, discharge energy efficiency and cycle performance are significantly better than those of the lithium iron phosphate material prepared by the traditional solid phase method in Comparative Example 1, proving that the uniformity of the primary particle size distribution can effectively ensure the consistency of the lithium iron phosphate material during the discharge process, thereby ensuring that the battery has a higher specific capacity, better rate performance, higher discharge energy efficiency and better cycle performance. Compared with the lithium iron phosphate material obtained by calcining the first dried material with a lower reaction temperature in Comparative Example 2, the specific capacity, rate performance, discharge energy efficiency and cycle performance of the lithium iron phosphate material prepared in Example 1 also have a significant increase. This is because the uniformity of the primary particle size distribution can obtain a lower powder resistivity, a higher compacted density and tap density, and a more moderate BET specific surface area, thereby ensuring that the specific capacity, rate performance, discharge energy efficiency and cycle performance of the material are comprehensively improved. At the same time, the 0.1C first charge specific capacity of the lithium iron phosphate material prepared in Examples 1 to 6 is ≥162.9 mAh / g, 0.1C first discharge specific capacity ≥159.2 mAh / g, 1C first charge specific capacity ≥148.3 mAh / g, 1C first discharge specific capacity ≥147.1 mAh / g, 0.5P discharge energy efficiency ≥95.30%, and the room temperature cycle capacity retention rate after 1000 cycles at a 1C rate is ≥98.2%. The charge and discharge specific capacity, discharge energy efficiency and cycle performance are significantly better than those of Examples 7 to 12, indicating that controlling the amount ratio of each raw material within a suitable range can further improve the uniformity of the primary particle size distribution of the lithium iron phosphate material, improve the compaction density and tap density, and reduce the powder resistivity, thereby exhibiting more excellent electrical properties.
[0257] In summary, the present application uses raw materials with low melting point and low decomposition temperature to prepare a first dry material with low chemical reaction temperature, and uses raw materials with high melting point and high decomposition temperature to prepare a second dry material with high chemical reaction temperature, and uses the difference in chemical reaction temperature of the two dry materials to realize the step-by-step nucleation and growth, avoiding the problem of extremely uneven primary particle size distribution caused by disordered growth and instantaneous rapid nucleation of lithium iron phosphate crystal nuclei, thereby preparing a lithium iron phosphate material with uniform primary particle size distribution and high concentration, which further exhibits the advantages of high specific capacity, good rate performance, high discharge energy efficiency and excellent cycle performance.
[0258] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A lithium iron phosphate material, characterized in that: The lithium iron phosphate material includes a core, the molecular formula of which is Li a Fe(PO4) b (BO3) c Among them, 1.02≤a≤1.05, 0.98≤b≤1.08, 0.01≤c≤0.02, and the number of particles with a primary particle size of 100nm~600nm accounts for ≥93.5%.
2. The lithium iron phosphate material according to claim 1, characterized in that: The diameter distance of the primary particles of the lithium iron phosphate material is 0.5-2.5, and the D50 particle size of the primary particles is 140nm-320nm; The compaction density of the lithium iron phosphate material is 2.20 g / mL to 2.60 g / mL, and the BET specific surface area of the lithium iron phosphate material is 8.0 m 2 / g~15.0m 2 / g, and the powder resistivity of the lithium iron phosphate material is 5.00Ω·cm~22.00Ω·cm.
3. The lithium iron phosphate material according to claim 1 or 2, characterized in that: The lithium iron phosphate material further includes a coating layer, and the coating layer is coated on the surface of the core; Wherein, the material of the coating layer includes a carbon material, and the mass percentage of the carbon material in the lithium iron phosphate material is 1.10% to 2.00%.
4. A method for preparing a lithium iron phosphate material, characterized in that: The following steps are involved: Mixing a ferrous source, an oxalate ion source, a borate ion source and a first regulator in a base liquid, and subjecting the mixture to a first reaction treatment; The mixture is subjected to a solid-liquid separation process and a first slurry process to obtain a first slurry; The first slurry is mixed with a first lithium source, a first phosphorus source and a second regulator, and then subjected to a first grinding treatment and a first drying treatment to obtain a first dried material; The trivalent iron source, the second phosphorus source, the second lithium source and the carbon source are mixed, and then subjected to a second slurrying process, a second grinding process and a second drying process to obtain a second dried material; The first dried material and the second dried material are mixed and then calcined to obtain the lithium iron phosphate material.
5. The method for preparing the lithium iron phosphate material according to claim 4, characterized in that: The step of mixing the ferrous source, the oxalate ion source, the borate ion source and the first regulator in the base liquid and obtaining the mixture through a first reaction treatment comprises: Mixing the ferrous source, the oxalate ion source, the borate ion source and the first regulator in a base liquid, and subjecting the mixture to a first treatment time at a first temperature to obtain the mixture; Wherein, the pH value of the base liquid is 4-5.5, the first temperature is 35° C.-55° C., and the first treatment time is 60 min-120 min.
6. The method for preparing the lithium iron phosphate material according to claim 4 or 5, characterized in that: The molar ratio of the iron element, oxalate and borate in the mixture is 1:(0.8-1):(0.1-0.2); The molar ratio of the iron element in the first slurry, the lithium element in the first lithium source, the phosphorus element in the first phosphorus source, and the second regulator is 1:(1.04-1.1):(1.04-1.1):(0.15-0.2); The molar ratio of the iron element in the trivalent iron source, the phosphorus element in the second phosphorus source, the lithium element in the second lithium source, and the carbon element in the carbon source is 1:1:(1.02-1.04):(1.2-1.8); The molar ratio of the lithium element in the first lithium source to the lithium element in the second lithium source is 1:(8-9).
7. The method for preparing the lithium iron phosphate material according to claim 6, characterized in that: The ferrous source is selected from at least one of ferrous sulfate, ferrous chloride and ferrous acetate, the oxalate ion source includes at least one of oxalic acid, ammonium oxalate and sodium oxalate, the borate ion source includes at least one of boric acid, ammonium borate and sodium borate, and the first regulator includes at least one of ammonium bicarbonate and sodium bicarbonate; The first phosphorus source is selected from at least one of phosphoric acid, diammonium hydrogen phosphate and ammonium dihydrogen phosphate, the first lithium source is selected from at least one of lithium oxalate and lithium acetate, and the second regulator includes at least one of polyethylene glycol, polyvinyl alcohol, polyvinyl pyrrolidone and polycarboxylic acid compounds; The ferric iron source includes ferric phosphate, the second phosphorus source includes ferric phosphate, the second lithium source includes lithium carbonate, and the carbon source is selected from at least one of glucose, sucrose, starch and cellulose.
8. The method for preparing the lithium iron phosphate material according to any one of claims 4 to 5 and 7, characterized in that: The step of mixing the first dried material and the second dried material and then calcining the mixture to obtain the lithium iron phosphate material comprises: The first dried material and the second dried material are mixed and then crushed to obtain a crushed material; The crushed material is subjected to a second treatment time at a second temperature in a first protective atmosphere, and then subjected to a third treatment time at a third temperature to obtain the lithium iron phosphate material; Among them, the D50 particle size of the first dried material is 2μm~5μm, the D50 particle size of the second dried material is 5μm~15μm, the D50 particle size of the crushed material is 0.5μm~1μm, the second temperature is 350℃~450℃, the second processing time is 2h~3h, the third temperature is 600℃~700℃, and the third processing time is 3h~6h.
9. A positive electrode sheet, characterized in that: It comprises a current collector and a positive electrode material arranged on at least one surface of the current collector along the thickness direction thereof, wherein the positive electrode material comprises the lithium iron phosphate material as claimed in any one of claims 1 to 3 or the lithium iron phosphate material prepared by the preparation method as claimed in any one of claims 4 to 8.
10. A secondary battery, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet and a separator, wherein the separator is arranged between the positive electrode sheet and the negative electrode sheet, and the positive electrode sheet is the positive electrode sheet according to claim 9.
Citation Information
Cited By
Lithium iron phosphate material and preparation method thereof, positive pole piece and secondary battery
CN120978063A
Positive electrode material, and preparation method therefor and use thereof
WO2026174519A1